APLIKASI SIMULASI UNTUK PERAMALAN PERMINTAAN DAN PENGELOLAAN PERSEDIAAN YANG BERSIFAT PROBABILISTIK - Sugiharto, Bambang (Industrial and Systems Engineering Assessment Journal (INASEA), 2007)
One of the important aspect on plan and production control is the management of inventory. However, a good inventory management is easily implemented, particularly when it involves some probabilistic parameter. There are two important parameters that usually behave probabilistically, those are demand and lead time. To overcome this situation, a simple methodology can be applied by determining an inventory model that can be used as a basic reference even though probabilistic situation exists. One of effective methods to make such a prediction is by using simulation. Among the simulation technique that can be applied are Monte Carlo simulation and Exponential Simulation.